2017
DOI: 10.1186/s13054-017-1876-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal wall fractional shortening: an M-mode index based on mitral annular plane systolic excursion (MAPSE) that correlates and predicts left ventricular longitudinal strain (LVLS) in intensive care patients

Abstract: BackgroundLeft ventricular longitudinal strain (LVLS) is a modern measurement for LV function. However, strain measurement is often difficult in critically ill patients. We sought to show LVLS can be estimated using M-mode-derived longitudinal wall fractional shortening (LWFS), which is less dependent on image quality and is easier to perform in critically ill patients.MethodsTransthoracic echocardiographic records were retrospectively screened and 80 studies suitable for strain and M-mode measurements in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…More sophisticated assessment of LV function beyond visual assessment may require training in advanced CCE. Other than mitral annular planar systolic excursion, which is a simple M-mode measurement, speckle tracking echocardiography and global longitudinal strain (GLS) are advanced measurements which may allow earlier diagnosis of septic cardiomyopathy and assist in prognostication [67][68][69]. Sanfilippo et al conducted a meta-analysis of eight studies, including 794 patients, that reported GLS and LVEF, and whilst LVEF did not show an association with mortality, worse GLS values (i.e.…”
Section: Cce For Prognostication In Septic Shockmentioning
confidence: 99%
“…More sophisticated assessment of LV function beyond visual assessment may require training in advanced CCE. Other than mitral annular planar systolic excursion, which is a simple M-mode measurement, speckle tracking echocardiography and global longitudinal strain (GLS) are advanced measurements which may allow earlier diagnosis of septic cardiomyopathy and assist in prognostication [67][68][69]. Sanfilippo et al conducted a meta-analysis of eight studies, including 794 patients, that reported GLS and LVEF, and whilst LVEF did not show an association with mortality, worse GLS values (i.e.…”
Section: Cce For Prognostication In Septic Shockmentioning
confidence: 99%
“…Such parameters have recently been shown to correlate strongly with GLS, with longitudinal wall fractional shortening being the best unbiased strain predictor. Given the simplicity of M-mode measurements, this may have significant clinical and practical implications for future critical care echocardiography investigations [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 TAPSE was also lower (although within normal range) in the severe group identifying early RV changes, while LVEF did not differ between groups. Huang et al 22 have recently showed that single BSA: body surface area; FEV 1 : forced expiratory volume in 1 second; lVDD: left ventricular diastolic diameter; lVSD: left ventricular systolic diameter; FS: left ventricle fractional shortening; lVEF: left ventricular ejection fraction; lA: left atria; E/A: mitral ratio of peak early to late diastolic filling velocity; RVSP: right ventricular filling pressure; TAPSE: tricuspid annular plane systolic excursion; RAP: right atrial pressure. Data are presented as mean (± SD) unless otherwise stated.…”
Section: Discussionmentioning
confidence: 99%